Eighth grade vs. the machines - Levy, Joshua (Joshua S.) (Carolrhoda Books, 2021)
"The entire population of Earth's solar system has been kidnapped by aliens. It's up to Jack and his classmates and teachers aboard the PSS 118 to rescue the rest of humanity"--